Perspektif Hukum Islam terhadap Adat Istiadat Mogama’ di Kelurahan Mogolaing: Perbedaan Nilai dengan Ajaran Islam - Suleman, Frangky; Soleman, Moh. Rafiq; Ontowirjo, Nurul Izzah Assyifa (Al-Mujtahid: Journal of Islamic Family Law, 2023)
This research aims to analyze the Islamic perspective on implementing the Mogama’ customary practices in Mogolaing Village, West Kotamobagu. A qualitative method was employed, conducting field research in Mogolaing Village, gathering data through observation, interviews, and documentation, which were analyzed based on information from the village head, customary leaders, religious figures, and community leaders. The research findings reveal differences in values between the Islamic interpretation and the practice of Mogama’ and Islamic law. Islamic teachings, such as respect for women, friendship, cooperation, blessings through congregational prayers, good treatment of women, and the development of strong familial ties, are not aligned with the values in Mogama’s practices. Some scholars discuss 'urf related to customs and traditions, utilizing 'urf and customs/practices appropriate to their context for adaptation. However, the traditional marriage procession of Bolaang Mongondow is considered in line with Islamic teachings as "Urf Saḥīh" because it does not contradict them. The research concludes that there are differences in values between Islamic teachings and Mogama’ practices. At the same time, some scholars use 'urf and customs/practices in their appropriate contexts for adaptation, and the traditional Bolaang Mongondow marriage is considered in accordance with Islamic teachings as 'Urf Saḥīh. Keywords: Mogama’; Sanctions; Islamic Law. ABSTRAKPenelitian ini bertujuan untuk menganalisis perspektif Islam terhadap penerapan adat istiadat Mogama’ di Kelurahan Mogolaing, Kotamobagu Barat. Metode kualitatif digunakan dengan penelitian lapangan di Kelurahan Mogolaing, mengumpulkan data melalui observasi, wawancara, dan dokumentasi yang dianalisis berdasarkan informasi dari kepala Kelurahan, tokoh adat, tokoh agama, dan tokoh masyarakat. Hasil penelitian menunjukkan perbedaan nilai antara penafsiran Islam terhadap praktik Mogama’ dan hukum Islam. Prinsip-prinsip ajaran Islam, seperti penghormatan terhadap perempuan, persahabatan, gotong royong, keberkahan melalui shalat berjamaah, perlakuan baik terhadap perempuan, dan pembangunan tali kekeluargaan erat, tidak selaras dengan nilai-nilai dalam praktik Mogama’. Beberapa ulama membahas ‘urf yang terkait dengan adat istiadat dan kebiasaan, menggunakan ‘urf serta adat/kebiasaan yang sesuai dengan konteksnya untuk menyesuaikan diri. Meskipun demikian, prosesi pernikahan adat Bolaang Mongondow dianggap sesuai dengan ajaran Islam sebagai "Urf Saḥīh" karena tidak bertentangan. Penelitian menyimpulkan bahwa terdapat perbedaan nilai antara ajaran Islam dan praktik Mogama’, sementara beberapa ulama menggunakan ‘urf dan adat/kebiasaan sesuai konteksnya untuk menyesuaikan diri, sementara pernikahan adat Bolaang Mongondow dianggap sesuai dengan ajaran Islam sebagai ‘Urf Saḥīh.